2019
DOI: 10.1101/726000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitroEvaluation of Various Antimicrobials against FieldMycoplasma gallisepticumandMycoplasma synoviaeIsolates in Egypt

Abstract: 28Among many avian mycoplasmas, Mycoplasma gallisepticum (MG) and 29 Mycoplasma synoviae (MS) are recognized as the main etiological agents of respiratory 30 diseases and infectious synovitis in chickens and turkeys causing tremendous economic 31 losses worldwide. Therefore, proper treatment is promoted for the control of these 32 diseases. This study was the first in Egypt to evaluate the in vitro efficacy of various 33 antimicrobials against field MG and MS isolates recovered from chicken and turkey 34 fl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…The maximum plasma level (C max ) of TVN after PO dosing to turkeys were 1.53 μg/mL and attained shortly (2 h) after administration. Additionally, the plasma concentration of TVN in the current study remained for 24 h higher than the MICs for TVN against several isolates of Mycoplasma gallisepticum (0.015–0.03 μg/mL) and Mycoplasma synoviae (0.015 μg/mL) isolated recently (Jan., 2017–Dec., 2018) from turkeys in Egypt (32) and TVN was found to be more effective than tilmicosin and tylosin in this study. Also, in another recent study (2014–2016), the MICs of TVN against 17 strains of Mycoplasma synoviae isolated from broiler turkeys originating from Central and Eastern Europe were ≤0.25 ug/mL (33).…”
Section: Discussionsupporting
confidence: 52%
“…The maximum plasma level (C max ) of TVN after PO dosing to turkeys were 1.53 μg/mL and attained shortly (2 h) after administration. Additionally, the plasma concentration of TVN in the current study remained for 24 h higher than the MICs for TVN against several isolates of Mycoplasma gallisepticum (0.015–0.03 μg/mL) and Mycoplasma synoviae (0.015 μg/mL) isolated recently (Jan., 2017–Dec., 2018) from turkeys in Egypt (32) and TVN was found to be more effective than tilmicosin and tylosin in this study. Also, in another recent study (2014–2016), the MICs of TVN against 17 strains of Mycoplasma synoviae isolated from broiler turkeys originating from Central and Eastern Europe were ≤0.25 ug/mL (33).…”
Section: Discussionsupporting
confidence: 52%
“…CO WT was formulated as 2 μg/ml. The result was similar to that of Landman et al (2008) who derived the unofficial CBP of S ≤ 1 and R ≥ 4 μg/ml for tylosin against MG ( Landman et al, 2008 ; Kreizinger et al, 2017 ; El-Hamid et al, 2019 ).…”
Section: Discussionsupporting
confidence: 85%
“…Abd El-Hamid et al [42] demonstrated that MG and MS infections can be controlled by proper treatment procedures. To develop an effective antibiotic treatment for MG and MS infections, we performed MIC experiments using eight different antimicrobials against five and three different MG and MS field isolates, respectively.…”
Section: Discussionmentioning
confidence: 99%